Time-domain impedance method for transient analysis and leakage detection in reservoir pipeline valve systems. (15th March 2022) - Kim, Sanghyun
Highlights: An alternative transient modelling and leakage detection approach is proposed. The time domain impedance function is introduced for the transient response. PSO is integrated into impedance calibration scheme addressing wide range of surge amplitudes. The leakage-identified impedance function substantially improves leakage detection. Numerical and experimental verifications demonstrate the superiority of the method. Abstract: An alternative approach to modeling the hydraulic transient response and leakage detection is proposed for reservoir pipeline valve systems. Exponential-function-based impedance formulations are derived in the frequency domain, which are useful for identifying the pressure response of different pipeline elements and abnormalities. The time-domain impedance function (TIF) is introduced to address the transient response for a specific pipeline system. The TIF comprehensively simulates various valve maneuvers or flowrates in either the laminar or turbulent flow regimes. The delineated TIF from the measured pressure head in the pipeline system with leakage exhibits potential for leak location prediction. The integration of the particle swarm optimization scheme into the inverse TIF algorithm provides a robust evaluation capability under a wide range of surge amplitudes. The developed leakage-identified impedance function substantially improves the leakage detection ability through transient impact isolation. Both the numerical and experimental verifications demonstrate the potential of the proposed method for leak detection as well as water hammer simulation for pipeline systems.